Analysis Of The Effect Of PSAK 73 Implementation On The Financial Performance Of Food And Beverage Companies Listed On The IDX In 2019-2021 - Marciano Marciano (Journal Research of Social Science, Economics, and Management, 2023)
The company's business activities are increasing and growing, creating a fairly tight business competition. In terms of accounting regulations, companies are also competing to apply records that are in accordance with standards for the benefit of stakeholders. The application of PSAK 73 itself Raja is a challenge for companies to implement in their business activities. This study aims to analyze the impact of implementing PSAK 73 on the financial performance of food and beverage companies listed on the Indonesian Stock Exchange for the 2019-2021 period. Financial performance will be measured by financial ratios such as ROA (Return on Assets), ROI (Return on investment), ROE (Return on Equity), Current Ratio and DER (Debt to Equity). The results showed that the ratios of ROA, ROI, ROE, Current Ratio and DER experienced significant differences after the implementation of PSAK 73.